2019
DOI: 10.3390/agronomy9120793
|View full text |Cite
|
Sign up to set email alerts
|

Mulching-Induced Changes in Tuber Yield and Nitrogen Use Efficiency in Potato in China: A Meta-Analysis

Abstract: In dry environments, potato (Solanum tuberosum L.) is grown under mulching for water conservation and improving tuber yield and nitrogen use efficiency (NUE). A meta-analysis was conducted to determine how mulching improved tuber yield and NUE in potato and how yield and NUE is influenced by fertilization, tillage practices, and growing environment in China. A search of peer-reviewed publications was performed to collect data on the effects of mulching on yield and NUE in potato grown in China. The data includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 49 publications
3
22
0
1
Order By: Relevance
“…Simulation of soil water and heat flow in ridge cultivation with plastic film mulching on the Chinese Loess Plateau decreased ET where plastic film mulching was less efficient practice for increasing WUE in dryland agriculture (Zhao et al, 2018). Plastic film mulching can provide conducive surroundings for attaining high potato yield (Wang et al, 2019) and facilitating maize grain filling hence maximizing yield (Liu et al, 2016). Consequently, plastic film mulched ridge-furrow approach may serve as a promising agronomic method in arid and semiarid regions to increase potato yield (Qin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Simulation of soil water and heat flow in ridge cultivation with plastic film mulching on the Chinese Loess Plateau decreased ET where plastic film mulching was less efficient practice for increasing WUE in dryland agriculture (Zhao et al, 2018). Plastic film mulching can provide conducive surroundings for attaining high potato yield (Wang et al, 2019) and facilitating maize grain filling hence maximizing yield (Liu et al, 2016). Consequently, plastic film mulched ridge-furrow approach may serve as a promising agronomic method in arid and semiarid regions to increase potato yield (Qin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Intercropping had increased LER and WER, especially for FMRFm/NMFp, which is consistent with the previous studies [5,7,37,38]. The mechanisms for high LER and WER in the maize/potato intercropping might be: (1) complementarity for water use between maize and potato due to the difference in root distribution of the component crops along with soil layer [37,38,49], for example, the roots of potato mainly distributes 0-40 cm soil layer [50], but the root system of maize can reach to 100 cm soil depth and could extract stored soil water from deeper soil layers [38], and complementarity for a light interception as a result of increased crop canopy architecture under the relatively low planting density in intercropping, leading to increased production of dry matter, thereby increased yields [7,17]; (2) potato is a shade loving crop [51][52][53], and thus aboveground shading from intercropped maize might be beneficial for the growth and yield. These changes under intercropping were beneficial towards promoting land productivity and water use efficiency when compared to monocropping.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [31] conducted a meta-analysis of 169 field studies to assess mulching effects on potato yield and nitrogen use efficiency (NUE) in arid climates. The results demonstrated that mulching significantly increased yield and NUE; however, combining organic fertilizers with mulching substantially reduced NPK fertilizer input without affecting potato yield or NUE.…”
Section: Nutrient Sourcesmentioning
confidence: 99%